# bobpursley,math

posted by
**jas20**
.

about this problem , I figured it out and i did get the answer right except that i had forgotten to make it a negative like this:

directions: subtract

4x-2x^2+4x^3 from 4x^3+x-3x^2

--------------------------------

4x^3-3x^2+x

-(4x^3-2x^2+4x)

---------------

so then it becomes

4x^3-3x^2+x

-4x^3+2x^2-4x

-------------

so then 4x^3 and -4x^3 = cancel out

and -3x^2 - 2x^2 = -x^2

and x - (-4x)=-3x

so the answer is: -x^2-3x

sorry for this part i did a typo:

I said it was this

so then 4x^3 and -4x^3 = cancel out

and -3x^2 - 2x^2 = -x^2

and x - (-4x)=-3x

BUt it should read like this only for this par:

4x^3 and -4x^3 = cancel out

-3+2=-1

and

1 + (-4)= -3

therefore the answer is: what i said on the previous message:

-x^2-3x

4x-2x^2+4x^3 from 4x^3+x-3x^2

4x^3+x-3x^2

-( 4x-2x^2+4x^3)

then changing signs and rearranging terms.

4x^3+x-3x^2

-4x^3-4x+2x^2

answer after ADDING the above..

-3x - x^2